Environmental changes since 14 ka BP in the southernmost Kuril islands (North-Western Pacific) and regional correlation of events. (1st April 2022) - Razjigaeva, Nadezhda G.; Ganzey, Larisa A.; Grebennikova, Tatiana A.; Mokhova, Ludmila M.; Rybin, Alexander V.; Nazarova, Larisa B.; Arslanov, Khikmatulla A.; Maksimov, Fedor E.; Petrov, Alexey Yu.; Zazovskaya, Elya P.
Highlights: New data on climatic changes at the late Pleistocene-Holocene boundary for Kurils. Climate fluctuations and volcanic ash-falls were mail drivers in lake-mire evolution. The lake level was highest during warmer and humid climate of the Allerød. Younger Dryas cooling in the Kuril Islands was less distinct than on the continent. Pollen record vegetation changes on the land bridge at Late Glacial–early Holocene. Abstract: Despite considerable progress in understanding Late Pleistocene and Holocene palaeoenvironmental changes worldwide, there are still very few such data for the Far East, and Kuril islands, in particular. Here, the sea level rise during the Late Glacial–Holocene transition was accompanied by a loss of the land connectivity culminating into the development of isolated islands. The ecosystems evolution and importance of isolation for vegetation dynamics on islands are still insufficiently understood. We investigated a unique natural record of environmental change since 14 ka has been recently discovered in lake–mire complex on Kunashir Island. The sediments include 12 tephra layers from Kunashir and Hokkaido volcanoes. The lake level was highest during warmer and humid climate of the Allerød. Diatom assemblages indicated the higher lake level between 12 730–12 160 cal yr BP. The first half of Younger Dryas was characterized by heavy snowfalls. Cooling attributed to the Younger Dryas in the Southern Kurils was less distinct than on the continent. The pollen assemblages recorded changes in vegetation on the land bridge. At the end of the Pleistocene large areas were occupied by birch forests and shrub pine. The broadleaf species first appeared at the end of Allerød. Starting from the Pleistocene-Holocene transition and during the early Holocene, the role of conifers sharply increased. In the middle Holocene the proportion of broadleaf trees in forests increased. Coniferous forests became abundant during the Little Ice Age. Short-tern climatic fluctuations correlate well with regional pattern, particularly with fluctuations of the moisture supply.